Galactosylated wall-teichoic acid, but not lipoteichoic acid, retains InlB on the surface of serovar 4b Listeria monocytogenes - Sumrall,ET; Schefer,CRE; Rismondo,J; Grundling,A; Boulos,S; Schneider,SR; Loessner,MJ; Shen,Y (Molecular Microbiology, 2020)
Listeria monocytogenes is a Gram-positive, intracellular pathogen harboring the surface-associated virulence factor InlB, which enables entry into certain host cells. Structurally diverse wall-teichoic acids (WTAs), which can also be differentially glycosylated, determine the antigenic basis of the various Listeria serovars. WTAs have many physiological functions; they can serve as receptors for bacteriophages, and provide a substrate for binding of surface proteins such as InlB. In contrast, the membrane-anchored lipoteichoic acids (LTAs) do not show significant variation and do not contribute to serovar determination. It was previously demonstrated that surface-associated InlB non-covalently adheres to both WTA and LTA, mediating its retention on the cell wall. Here, we demonstrate that in a highly virulent serovar 4b strain, two genes gtlB and gttB are responsible for galactosylation of LTA and WTA, respectively. We evaluated the InlB surface retention in mutants lacking each of these two genes, and found that only galactosylated WTA is required for InlB surface presentation and function, cellular invasiveness, and phage adsorption, while galactosylated LTA plays no role thereof. Our findings demonstrate that a simple pathogen-defining serovar antigen, that mediates bacteriophage susceptibility, is necessary and sufficient to sustain the function of an important virulence factor.